Pengukuran Kinerja Sumber Daya Manusia Dengan Pendekatan Human Resources Scorecard dan Analytical Hierarchy Process : Studi Kasus di PT. XYZ - Dahman, Muhamad; Aulawi, Hilmi (Jurnal Kalibrasi, 2025)
PT. XYZ is a bakery and pastry company established in 2007. The main problem arises in the production process, where the target number of workers in the marchies division is 104, but only 97 are available. Efforts to reassign personnel from the bagelen team have still not met the target. In addition, employee absenteeism remains an obstacle. To date, the company has never conducted a comprehensive measurement of employee performance. This study aims to measure employee performance comprehensively and improve underperforming indicators using the Human Resource Scorecard (HRSC) and Analytical Hierarchy Process (AHP) methods. The results identified 10 Key Performance Indicators (KPIs): 2 from the financial perspective, 3 from the customer perspective, 3 from internal business processes, and 2 from growth and learning. Based on the AHP results, the customer perspective emerged as the top priority, with the turnover rate as its main indicator. Turnover is in the red category, requiring urgent improvement, while employee absenteeism is in the yellow category, which also needs corrective action. The recommended strategy to reduce turnover is the implementation of a comprehensive onboarding program to help new employees quickly adapt to the company’s culture and work system. Additionally, workload should be evaluated every six months, and the work culture should be strengthened through regular workshops and team-building activities. To address absenteeism, the company can introduce attendance-based incentive programs, analyze the reasons behind absences, improve workplace facilities, and reinforce the attendance policy with clear sanctions and proper leave management.